USING SONGS TO TEACH ENGLISH TO YOUNG LEARNERS - Aulia Fransischa; An Fauzia Rozani Syafei (Universitas Negeri Padang, 2016)
This paper explains about the implementation of using songs to teach English to young learners. The songs that can be used are popular songs for young learners. At the beginning of the activity, teacher introduces the lyrics that will be sung. The lyrics of the song should be compared with the topic. The activity of singing a song can be followed by another activities which the activities can improve their confidence. There are some advantages in teaching English through songs like various activities in the classroom, fun, and alive, also the young learners be active and confidence. Then, songs can improve the young learner’s skill in memorizing new words and pronouncing clearly. Using songs as the activity in teaching English help the teacher to build an active and interesting class.